PP11 An audit of match day injuries in a semi-professional rugby union team. (21st October 2014) - Smith, R; Thompson, H; Goodman, M
Abstract : This prospective audit establishes the incidence (per 1000 player match hours) and severity of injuries (time lost and matches missed) at a semi-professional rugby union club (SPRUC). Over the season of 2013/14 injury information regarding event, type, playing position and severity (number of days missed through injury) for all senior male first team players was recorded by medical staff using the Benchmark 54 injury analytics software. Similar to Roberts et al. (BMJ Open 2013;3:e003998) any injury resulting in 8 days or greater absence from match play was recorded. Type of injury was recorded using the Orchard Sports Injury Classification System v10 (Rae et al . Br J Sports Med 2005; 39 :907–11). Written consent was gained from every player. There were a total of 35 injuries with an injury rate of 1.06 per match. The overall match injury incidence was 54.1/1000 playing hours. Median for time loss from an injury was 30 days and the median number of games missed through injury was three. The most common sites of injury were ankle, knee and shoulder. Contact events accounted for 77% (27/35) of all injuries, of these 60% (17/27) were sustained in the tackle. Joint and ligament injuries were the most frequent type accounting for just under half of all injuries. Fractures caused the greatest time loss with a player missing a mean of 14 games. This audit has recorded a high number of time loss injuries which are costly to the club. This information can help SPRUCs plan for squad sizes and adequate medical staffing. Interventions should focus on injury prevention strategies regarding the tackle event and conditioning exercises for the knee, shoulder and ankle. Further work should examine training injuries and completion of the audit cycle.